2003
DOI: 10.1002/jcp.10273
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of Photofrin® determines the death phenotype of human epidermoid carcinoma A431 cells triggered by photodynamic therapy: When plasma membranes are the main targets

Abstract: Photodynamic therapy (PDT) is a kind of photochemo-therapeutic treatment that exerts its effect mainly through the induction of cell death. Distinct types of cell death may be elicited by different PDT regimes. In this study, the mechanisms involved in the death of human epidermoid carcinoma A431 cells triggered by PDT with Photofrin (a clinically approved photosensitizer) were characterized. Photofrin distributes dynamically in A431 cells; the plasma membranes and Golgi complex are the main target sites of Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
126
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(143 citation statements)
references
References 44 publications
9
126
2
Order By: Relevance
“…Upon excitation, the photosensitizers generate ROS (primarily singlet oxygen) that can lead to cell death [146,147]. When photosensitization compounds localize to the plasma membrane, cells die by necrosis resulting from the loss of plasma membrane integrity [148,149]. Activation of photosensitizers on lysosomes may disrupt the lysosomal membrane and result in the release of lysosomal proteases leading to necrosis [150].…”
Section: Activating Necrosismentioning
confidence: 99%
“…Upon excitation, the photosensitizers generate ROS (primarily singlet oxygen) that can lead to cell death [146,147]. When photosensitization compounds localize to the plasma membrane, cells die by necrosis resulting from the loss of plasma membrane integrity [148,149]. Activation of photosensitizers on lysosomes may disrupt the lysosomal membrane and result in the release of lysosomal proteases leading to necrosis [150].…”
Section: Activating Necrosismentioning
confidence: 99%
“…The susceptibility of TPPS 2a -PDT mediated EGFR damage seems to be cell line Photofrin (Wong et al 2003), 5-ALA induced protoporphyrin IX (PpIX) (Wong et al 2003), Hypericin (de Witte et al 1993) and RB (Zhuang et al 2003, Schieke et al 2004 as PSs may be caused by a direct oxidation of the receptor at light exposure time, as all of these PSs has been shown to localize to the plasma membrane (Thomas & Pardini 1992, Lin et al 2000, Selbo et al 2001a, Hsieh et al 2003b. In addition, the lipophilicity of these PSs indicate that they can freely diffuse through the plasma membrane, and thereby easily target the intracellular domain of EGFR upon light exposure.…”
Section: Tpps 2a -Pdt Induced Damage To Egfrmentioning
confidence: 99%
“…Assefa et al reported that JNK activation rescues cells from hypericin mediated PDT (Assefa et al 1999) while JNK activation after Photofrin-PDT has been shown not to influence on cytotoxicity (Hsieh et al 2003a). P38 is also a stress induced kinase (Zarubin & Han 2005) shown to be activated after PDT with different photosensitizers.…”
Section: The Impact Of Mapk Signallingmentioning
confidence: 99%
“…It has been assumed that photosensitisers primarily localised in mitochondria are able to induce early apoptosis by rapid loss of mitochondrial transmembrane potential and/or release of apoptosis-inducing factors such as cytochrome c (cyt c), itself leading to post-mitochondrial caspase activation (Kessel and Luo, 1999;Chiu and Oleinick, 2001). Several reports investigated the possibility to modulate the mechanism of PDTinduced cell death using protocols that selectively target proapoptotic organelles (Fabris et al, 2001;Hsieh et al, 2003). Prolonged incubation of photosensitisers (24 h) with cells compared with shorter incubation times (2 -3 h) was accompanied by a more efficient apoptosis after photoirradiation.…”
mentioning
confidence: 99%
“…Prolonged incubation of photosensitisers (24 h) with cells compared with shorter incubation times (2 -3 h) was accompanied by a more efficient apoptosis after photoirradiation. This was attributed to photosensitiser relocalisation to mitochondria or Golgi apparatus during incubation (Fabris et al, 2001;Hsieh et al, 2003).…”
mentioning
confidence: 99%